Nutrition and educational achievement of urban primary schoolchildren in Malaysia - Mohd Shariff, Zalilah; Bond, Jenny T; Johnson, Nan E (Wiley, 2001)
The relationship between nutrition, health and educational achievement of school‐age population in less developed countries has been of interest to many researchers due to the frequent observation that many children did not complete primary school and those who completed, did not do as well as children in the developed countries. Nevertheless, nutritional and health status by itself is not the only variable affecting educational achievement, since biological, psychological, socioeconomic and cultural factors could directly or indirectly affect both nutrition, health status and educational achievement. The mechanism by which health and nutrition influence educational achievement is not well established, but poor health and malnutrition in early childhood may affect cognitive abilities, necessary for learning process and consequently educational achievement. A study was conducted in Kuala Lumpur, Malaysia, to investigate the relationship between nutritional status and educational achievement among primary schoolchildren from low income households ( n = 399). A high percentage of them were mild‐significantly underweight (52%), stunted (47%) and wasted (36%) and increasingly overweight (6%). In general, more boys than girls were found to experience some form of malnutrition. While weight‐for‐height did not differ significantly according to family, child and school factors, weight‐for‐age and height‐for‐age differed significantly by gender. Also, height‐for‐age was significantly related to household income. This indicates that stunting may be a consequence of prolonged socioeconomic deprivation. Educational achievement was measured based on test scores for Malay language (ML), English language (EL) and mathematics (MT). While a majority of the schoolchildren obtained optimum scores (>75) for ML and MT, the majority of them had insufficient scores (<50) for EL. Children’s total score (TS) for the three subjects was significantly associated with household socioeconomic status, gender, birth order and height‐for‐age. Even after controlling for household socioeconomic status, significant association between TS and height‐for‐age persisted. In this sample of schoolchildren, household income, gender, birth order and height‐for‐age were significant predictors of TS. The finding that height‐for‐age is related to educational achievement agrees with other studies, which have reported that height‐for‐age, compared to weight‐for‐height or weight‐for‐age is linked to educational achievement. Height‐for‐age reflects the accumulation of nutritional deprivation throughout the years, which may consequently affect the cognitive development of the children.